An Integrated Biorefinery Process to Revalorize Marine Biomass from the Microalga Nannochloropsis gaditana Using Pressurized Green Solvents - Cristina Blanco-Llamero; Paz García-García; Francisco Javier Señoráns (Marine Drugs)
Biorefinery is gaining attention as a promising approach to valorize natural resources and promote a circular bioeconomy. This study aimed to recover high-value molecules, such as xanthophylls and polar lipids with nutraceutical applications, through enzymatic pretreatment and sequential pressurized liquid extraction (PLEseq), by reusing the residual biomass of Nannochloropsis gaditana after each processing step. Remarkably, pure glycolipids (102.95 ± 1.10 mg g−1 dry weight) were obtained immediately after enzymatic pretreatment, facilitating their easy recovery. Furthermore, two alternative sequential extraction processes were successfully developed, using ethanol and water as green solvents at varying temperatures and in different orders. The most effective PLEseq conditions yielded up to 48 mg mL−1 of carbohydrates using water at 50 °C, and up to 44 mg mL−1 of proteins via subcritical water extraction at 100 °C, prior to conventional lipid extraction with ethanol to produce various concentrated extracts. In the inverted PLEseq process—starting with ethanol extraction followed by successive water washes—isolated and purified fractions of lutein and astaxanthin were obtained, contributing to the complete depletion of the residual biomass. Overall, the development of an integrated and sequential biorefinery protocol that enables the extraction of multiple high-value compounds holds significant potential for application in the food industry.